Sequencing of human genomes extracted from single cancer cells isolated in a valveless microfluidic device. Issue 13 (6th June 2018) - Marie, Rodolphe; Pødenphant, Marie; Koprowska, Kamila; Bærlocher, Loic; Vulders, Roland C. M.; Wilding, Jennifer; Ashley, Neil; McGowan, Simon J.; van Strijp, Dianne; van Hemert, Freek; Olesen, Tom; Agersnap, Niels; et al.
Abstract : Whole genome sequencing of single cancer cells isolated and lysed in an injection-moulded valveless microfluidic device. Abstract : Sequencing the genomes of individual cells enables the direct determination of genetic heterogeneity amongst cells within a population. We have developed an injection-moulded valveless microfluidic device in which single cells from colorectal cancer derived cell lines (LS174T, LS180 and RKO) and fresh colorectal tumors have been individually trapped, their genomes extracted and prepared for sequencing using multiple displacement amplification (MDA). Ninety nine percent of the DNA sequences obtained mapped to a reference human genome, indicating that there was effectively no contamination of these samples from non-human sources. In addition, most of the reads are correctly paired, with a low percentage of singletons (0.17 ± 0.06%) and we obtain genome coverages approaching 90%. To achieve this high quality, our device design and process shows that amplification can be conducted in microliter volumes as long as the lysis is in sub-nanoliter volumes. Our data thus demonstrates that high quality whole genome sequencing of single cells can be achieved using a relatively simple, inexpensive and scalable device. Detection of genetic heterogeneity at the single cell level, as we have demonstrated for freshly obtained single cancer cells, could soon become available as a clinical tool to precisely match treatment with the properties of a patient's own tumor.